Prevalence and severity of temporomandibular disorders among university students in Riyadh - Syed Rashid Habib; Mohammad Qasim Al Rifaiy; Kamran Habib Awan; Abdulaziz Alsaif; Abdulaziz Alshalan; Yasser Altokais (Saudi Dental Journal)
Objective: The aim of this study was to evaluate the prevalence and severity of temporomandibular disorders (TMDs) among male university students in Riyadh, Saudi Arabia. The role of relevant medical and dental histories in the assessment of TMD in this Arab population was also addressed. Methods: Required information was collected via a questionnaire. The first part of the questionnaire was used to obtain the medical and dental histories of participants. The second part included 10 questions regarding common TMD symptoms. Fonseca’s anamnestic index (FAI) was used to classify TMD severity as “no dysfunction”, “light dysfunction”, “moderate dysfunction”, or “severe dysfunction”. Results: Of the 600 distributed questionnaires, 400 questionnaires were completed (response rate: 66.6%). Mean age of eligible participants was 21.90 ± 1.79 years. Psychological stress (30.5%) and direct restorations (77%) were the most commonly reported items on the medical and dental histories respectively for the total number of participants. According to the FAI, 53.2% of participants were classified as having no dysfunction, followed by light (36.1%), moderate (9.6%), and severe dysfunction (1.1%). Conclusions: Based on the FAI, mild to moderate prevalence of TMD appears to exist among male university students in Riyadh. Histories of psychological stress and dental treatment were evident among these students. Information obtained from the FAI may be helpful in assessing the prevalence of TMD and has important implications for the early diagnosis of TMD and the prevention of future TMD-related complications. Keywords: Temporomandibular disorder, Temporomandibular joint, TMDs, Fonseca’s questionnaire, Fonseca’s anamnestic index, Cross-sectional survey